Public health and social measures to mitigate the health and economic impact of the COVID-19 pandemic in Turkey, Egypt, Ukraine, Kazakhstan, and Poland during 2020-2021: situational analysis - Noriko Kitamura; Kaja Abbas; Dilip Nathwani (BMC, 2022)
Abstract Background The COVID-19 pandemic had a colossal impact on human society globally. There were similarities and differences in the public health and social measures taken by countries, and comparative analysis facilitates cross-country learning of contextual practices and sharing lessons to mitigate the COVID-19 pandemic impact. Our aim is to conduct a situational analysis of the public health and social measures to mitigate the health and economic impact of the COVID-19 pandemic in Turkey, Egypt, Ukraine, Kazakhstan, and Poland during 2020-2021. Methods We conducted a situational analysis of the COVID-19 pandemic response in Turkey, Egypt, Ukraine, Kazakhstan, and Poland from the perspectives of the health system and health finance, national coordination, surveillance, testing capacity, health infrastructure, healthcare workforce, medical supply, physical distancing and non-pharmaceutical interventions, health communication, impact on non-COVID-19 health services, impact on the economy, education, gender and civil liberties, and COVID-19 vaccination. Results Since the onset of the COVID-19 pandemic, Turkey, Egypt, Ukraine, Kazakhstan, and Poland have expanded COVID-19 testing and treatment capacity over time. However, they faced a shortage of healthcare workforce and medical supplies. They took population-based quarantine measures rather than individual-based isolation measures, which significantly burdened their economies and disrupted education. The unemployment rate increased, and economic growth stagnated. Economic stimulus policy was accompanied by high inflation. Despite the effort to sustain essential health services, healthcare access declined. Schools were closed for 5-11 months. Gender inequality was aggravated in Turkey and Ukraine, and an issue was raised for balancing public health measures and civil liberties in Egypt and Poland. Digital technologies played an important role in maintaining routine healthcare, education, and public health communication. Conclusions The COVID-19 pandemic has exposed weaknesses in healthcare systems in the emerging economies of Turkey, Egypt, Ukraine, Kazakhstan, and Poland, and highlighted the intricate link between health and economy. Individual-level testing, isolation, and contact tracing are effective public health interventions in mitigating the health and economic impact of the COVID-19 pandemic in comparison to population-level measures of lockdowns. Smart investments in public health, including digital health and linking health security with sustainable development, are key for economic gain, social stability, and more equitable and sustainable development.